Sistem Pewarisan Tenun Sasak sebagai Pendidikan Budaya Sasak - Khairul Fahmi; Indar Sabri; Haris Supratno; Welly Suryandoko; Autar Abdillah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
One of Indonesia's cultural heritages that deserves to be preserved is the art of weaving, which symbolizes identity and local wisdom, especially among the Sasak tribe in Lombok. Weaving is not just a skill, but also rich in cultural and spiritual values. For Sasak women, weaving skills are even an important requirement in marriage. The weaving tradition in Pringgasela Village, East Lombok, faces significant challenges in its preservation. Changes in lifestyle toward modernization, a lack of regeneration among the younger generation, and low income from weaving products have led to a decline in interest in the art of weaving. This study aims to explore the role of Sasak women in preserving and passing down the weaving tradition as part of Sasak cultural education. The research findings indicate that while there are groups of women who remain committed to preserving this tradition, external factors such as modernization and competition from industrial products are affecting the sustainability of the weaving tradition. Therefore, support from the government and society is needed to preserve and maintain the art of weaving so that it remains an integral part of Indonesia's cultural identity.